Cities back to the river: the neglect of urban PPAs in the Cuiabá River Valley Metropolitan Region - RMVRC/MT - Salmoria, Fabiana Zili; Godoy, Jeane Aparecida Rombi de (Revista Nacional de Gerenciamento de Cidades, 2022)
This research studied the process of irregular urban occupations that occurred along the Cuiabá River Permanent Preservation Areas (PPAs), as a key to understand its importance for urban sustainability. Its objective was to study the dynamics and socio-environmental impacts resulting from irregular occupations along the banks of the river that cuts through the two largest cities in the Metropolitan Region of the Cuiabá River Valley - RMVRC/MT, the state capital Cuiabá, and Várzea Grande. Considering that this river is responsible for the water supply of both cities, and a Pantanal Mato-Grossense affluent, which have a fundamental relevance for the local and regional ecosystem, it became important to identify the contradictory relationships between socio-environmental issues and the application and surveillance of urban legislation, by mapping the APPs, in order to verify the degradation of the Cuiabá River. The methodology was based on bibliographic, documental and empirical research. The results showed the importance of its continuity in new research, and may also subsidize decision-making processes, formulation of urban and environmental legislation, public policies aimed at socio-environmental protection of vulnerable areas, relevant to improving the quality of life and the environment.